Investigation Of Transmittance And Hydrophobic Properties Of SiO:ZNO:SiO2 As A Multilayer Coating Substance - Nasrullah Nazri; Sofina Tamam (Malaysian Solid State Science and Technology Society, 2024)
Volume :27 No:1 &2